PENGARUH EMPLOYEE ENGANGEMENT DAN LINGKUNGAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN MEDIASI KOMITMEN ORGANISASIONAL - Budi Sulistyawan, 1342020033 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze the effect of employee engangement and work environment to organizational citizenship behavior with the mediation organizational commitment to agricultural extension in distric of Demak. The technique of testing data used in this study include validity, reliability, multiple regression analysis, model test, t test and mediation to test and prove the research hypothesis. Based on the results of the analysis and discussion shows that employee engangement positive and significant impact on organizational commitment. Work environment does not affect the organizational commitment. Employee engangement positive and significant effect on organizational citizenship behavior. Work environment positive and significant effect on organizational citizenship behavior. Organizational commitment positive and significant effect on organizational citizenship behavior. Engangement employee influence and the work environment against stronger organizational citizenship behavior directly than through the mediation of organizational commitment